Opini Audit,Transparansi dan Akuntabiltas Terhadap Minat Membayar Zakat Dengan Kesadaran Zakat Sebagai Variabel Intervening - Ayu Ruqayyah Yunus; Abdul Wahab; Mochammad Fadhil Abdullah; Adhifa Ananda (LAA MAISYIR: Jurnal Ekonomi Islam, 2023)
In 2022, the emergence of a scandal revealed by the media related to social donation collection institutions, namely the rapid response action (ACT) has shocked the public regarding the poor management of the social funds they manage. This phenomenon indicates a failure of integrity. As a result, the image is negative to similar institutions including amil zakat institutions. This research was conducted to determine the influence of audit opinions, transparency, and accountability on the interest in paying zakat with awareness as an intervening variable in BAZNAS Makassar City. This research method is quantitative with a sample of 196 respondents. Data processing using the SmartPLS 4.0 application. The results of the study concluded partially transparency, and accountability directly has a positive and significant influence on the interest in paying zakat in Baznas Makassar City. Meanwhile, Audit Opinion and Awareness do not influence the interest in paying zakat. The influence of awareness variables in this study was unable to mediate Audit Opinion, Transparency, and Accountability on the interest in paying zakat at the National Amil Agency (Baznas) Makassar City.